Application of Biosheets as Right Ventricular Outflow Tract Repair Materials in a Rat Model - Mizuno, Takeshi; Iwai, Ryosuke; Moriwaki, Takeshi; Nakayama, Yasuhide (Frontiers in Veterinary Science, 2022)
Purposes We report the experimental use of completely autologous biomaterials (Biosheets) made by “in-body tissue architecture” that could resolve problems in artificial materials and autologous pericardium. Here, Biosheets were implanted into full-thickness right ventricular outflow tract defects in a rat model. Their feasibility as a reparative material for cardiac defects was evaluated. Methods As the evaluation of mechanical properties of the biosheets, the elastic moduli of the biosheets and RVOT-free walls of rats were examined using a tensile tester. Biosheets and expanded polytetrafluoroethylene sheet were used to repair transmural defects surgically created in the right ventricular outflow tracts of adult rat hearts (n = 9, each patch group). At 4 and 12 weeks after the operation, the hearts were resected and histologically examined. Results The strength and elastic moduli of the biosheets were 421.3 ± 140.7 g and 2919 ± 728.9 kPa, respectively, which were significantly higher than those of the native RVOT-free walls (93.5 ± 26.2 g and 778.6 ± 137.7 kPa, respectively; P < 0.005 and P < 0.001, respectively). All patches were successfully implanted into the right ventricular outflow tract-free wall of rats. Dense fibrous adhesions to the sternum on the epicardial surface were also observed in 7 of 9 rats with ePTFE grafts, whereas 2 of 9 rats with biosheets. Histologically, the vascular-constructing cells were infiltrated into Biosheets. The luminal surfaces were completely endothelialized in all groups at each time point. There was also no accumulation of inflammatory cells. Conclusions Biosheets can be formed easily and have sufficient strength and good biocompatibility as a patch for right ventricular outflow tract repair in rats. Therefore, Biosheet may be a suitable material for reconstructive surgery of the right ventricular outflow tract.